The first imported case of monkeypox in Singapore during the 2022 outbreak – Reflections and lessons. Issue 50 (November 2022) - Tan, Wilnard Yeong Tze; Wong, Chen Seong; Ho, Marc Zheng Jie; Said, Zubaidah; Cui, Lin; Lin, Raymond Tzer Pin; Chan, Monica; Vasoo, Shawn; Lee, Vernon Jian Ming; Leo, Yee Sin
Abstract: On June 21, 2022, Singapore reported its second ever case of imported monkeypox and first linked to the ongoing multi-country outbreak that has since been declared a public health emergency of international concern. There was quick initiation of public health measures including identification and quarantine of contacts, with post-exposure smallpox vaccination.